2003
DOI: 10.1063/1.1578183
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of Co:ZnO films deposited from Zn and Co metal targets on (0001) Al2O3 substrates

Abstract: We report on the synthesis of high-quality Co-doped ZnO thin films using the pulsed laser deposition technique on (0001)-Al 2 O 3 substrates performed in an oxidizing atmosphere, using Zn and Co metallic targets. We firstly optimized the growth of ZnO in order to obtain the less strained film. Highly crystallized Co:ZnO thin films are obtained by an alternative deposition from Zn and Co metal targets. This procedure allows an homogenous repartition of the Co in the ZnO wurzite structure which is confirmed by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
115
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 18 publications
9
115
1
2
Order By: Relevance
“…Ueda et al 7 reported T c above 280 K for Codoped ZnO, but the reproducibility was less than 10%. Prellier et al 8 observed ferromagnetism with T c close to room temperature in 5% Co-doped ZnO. Ferromagnetism with T c above 350 K was found in films fabricated by the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda et al 7 reported T c above 280 K for Codoped ZnO, but the reproducibility was less than 10%. Prellier et al 8 observed ferromagnetism with T c close to room temperature in 5% Co-doped ZnO. Ferromagnetism with T c above 350 K was found in films fabricated by the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…For films doped with 3-25 at % Ni, ferromagnetism was observed at 2 K. 5 Ferromagnetic behavior with T c higher than 350 K was found in V-doped ZnO films fabricated by pulsed laser deposition. 6 As to Co-doped ZnO, a few papers appeared recently, [7][8][9][10][11] but the results are controversial. Ueda et al 7 reported T c above 280 K for Codoped ZnO, but the reproducibility was less than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…%, 19 25-30 at. %, 14,17 and lower 10,11,13,27 Co concentrations, others reported the absence of ferromagnetism at room temperature. 8,15,25 In this paper we report detailed studies using various experimental techniques for the investigation of the structural, magnetic, and electronic properties of Co-implanted ZnO films grown on sapphire substrates and for different a͒ Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…5,11,15,24 Various solubility limits for Co in ZnO were reported by different groups. Prellier et al 10 determined a solubility limit of about 10 at. % in PLD-grown films.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous studies the ferromagnetic properties of transition metal cations doped wurtzite ZnO host is still a controversial issue [1][2][3][4][5][6]. A high temperature ferromagnetism was reported numerously for Co doped ZnO in thin films produced by all accessible methods including pulsed layer deposition [7], the magnetron co-sputtering [8], the solgel method [9], and epitaxial thin films [10]. Recently, Fe doped ZnO nanostructures, synthesized by the sol-gel method, were observed to be ferromagnetic [11].…”
Section: Introductionmentioning
confidence: 99%